The Association Between Glucocorticoid Administration and the Risk of Impaired Efficacy of Axicabtagene Ciloleucel Treatment: A Systematic Review - Sun, Zhen; Xun, RenDe; Liu, MengSi; Wu, XiaoQin; Qu, HongTao (Frontiers in Immunology, 2021)
Background Glucocorticoid is one of the common and important strategies for the treatment of chimeric antigen receptor T (CAR-T) cell therapy-related toxicity. However, there has been a theoretical concern about whether glucocorticoids use can impact the expansion of CAR-T cells and thus impair its efficacy. Hence, we reviewed studies related to the Axicabtagene ciloleucel (Axi-cel), a first-class and widely used CAR-T cell product, to elucidate the association between glucocorticoids administration and efficacy of Axi-cel. Method We systematically searched PubMed, Embase, Web of Science, and Cochrane Library to identify studies of Axi-cel that used glucocorticoids as an intervention for the treatment of CAR-T cell-related adverse events and respectively evaluated any efficacy endpoints of intervention and controlled cohorts, published up to February 17, 2020. There were no restrictions on research type and language. Results A total of eight studies with 706 patients were identified in the systematic review. Except for one study found that high cumulative dose, prolonged duration and early use of glucocorticoids could shorten progression-free survival and/or overall survival, and another study that found a negative effect of glucocorticoids administration on overall survival in univariate analysis but disappeared in multivariate analysis, none of other studies observed a statistically significant association between glucocorticoids administration and progression-free survival, overall survival, complete response, and overall response rate. Conclusion Our study indicated that the association between glucocorticoids therapy and the efficacy of CAR-T cell may be affected by cumulative dose, duration, and timing. There is currently no robust evidence that glucocorticoids can damage the efficacy of CAR-T cell, but the early use of glucocorticoids should be cautiously recommended.